Urban pedestrian mall : Socio-economic and environmental implications / Idrus Abdul Shukor - Abdul Shukor, Idrus (1983)
The degrading quality of urban life in Georgetown could well be associated with the encroachment of traffic. More people are turning to the suburbs to escape the hostile urban environment. The downtown retail activities are left dilapidated physically and economically depressed while the shopping complexes prosper under such an environment. The Penang City Council feels that the implementation of a pedestrianization program would solve the problem but it is opposed by the retailers and some of the customers. To uncover the reasons for such negative responses, the retailers opinion survey and the public opinion survey are conducted. The data from the surveys are used to evaluate the performance of the previous mall experiments and also the response of the users towards the proposed mall program. The main problem affecting the effectiveness of the previous mall experiments relates to the lack of comprehensive planning done prior to those mall experiments. The users requirements are not adequately accommodated for and potential problems are not forseen. The previous mall experiments have also failed to incorporate community involvement in the planning, implementation and management programs…